MANAJEMEN MUTU PELAYANAN PENDIDIKAN - Edhi Wasisto (STIE AUB Surakarta, 2013)
This study aimed to determine the effect of service quality in terms of the dimensions of tangibles, reliability, responsiveness, assurance, empathy and body image influenced on student loyalty with satisfaction as an intervening variable. Data were collected from 42 respondents using accidental sampling method sampling. Data analysis was carried out through analysis of research instruments that include test 0f validity of using the product moment correlation and reliability testing using Cronbach's alpha technique, the normality test, test lineritas, hypothesis test includes multiple linear regression, t test, F test and coefficient of determination (R2).